'Regurgitation and reingestion' (R/R) in great apes: a review of current knowledge. Issue 1 (2nd August 2018) - Hill, S. P.
Abstract : Research indicates that regurgitation and reingestion (R/R) is a relatively common behaviour in zoo‐housed great apes, with most studies to date carried out on Western lowland gorillas Gorilla gorilla gorilla and Chimpanzees Pan troglodytes . R/R is an abnormal behaviour because great apes are not anatomically adapted to regurgitate their food as part of their normal feeding processes, and because this behaviour has not been observed in members of the species living freely in the wild, in conditions that would allow a full behavioural range. In this article, an overview is given of the published literature on R/R in great apes, which suggests that this behaviour is probably multifactorial and may be linked to inappropriate feeding environments (e.g. in terms of nutritional composition of the diet and/or presentation of food), and possibly also social and other factors. A similar behaviour to R/R, known as rumination disorder, can occur in humans (another great ape species), in whom it is classified as a feeding and eating disorder, and there are potential consequences to people's physical health as a result of oral acid. There have been no known studies to date to identify whether or not similar health consequences can occur in non‐human great apes, but the regurgitant has been found to be significantly more acidic in gorillas than the food they ingested originally, meaning it is potentially injurious in non‐human great apes. There is much that is not yet known about R/R and how to reduce or eliminate it when it does occur. The research indicates that there are a range of factors involved and these can vary by individual animal. More research into this behaviour is clearly needed to ensure that zoos and sanctuaries are providing the best possible care for these animals, and some suggestions for future research directions are included in this review. Abstract : Research indicates that regurgitation and reingestion (R/R) is a relatively common behaviour in zoo‐housed great apes, with most studies to date carried out on Western lowland gorillas Gorilla gorilla gorilla and Chimpanzees Pan troglodytes . R/R is an abnormal behaviour because great apes are not anatomically adapted to regurgitate their food as part of their normal feeding processes, and this behaviour has not been observed in free‐living conspecifics. An overview of the published literature on R/R in great apes is provided, which suggests that this behaviour is probably multifactorial and may be linked to inappropriate feeding environments, as well as social and other factors. More research into this behaviour is clearly needed to ensure that zoos and sanctuaries are providing the best possible care for great apes, and some suggestions for future research directions are included in this review. (Photo: Sonya P. Hill)